Keefektifan Senyawa Bioaktif Klon Pustaka Metagenomik sebagai Biokontrol Meloidogyne incognita dan Pemacu Pertumbuhan Tanaman: Effectiveness of the Bioactive Compound from Metagenomic Library Clones as Biocontrol of Meloidogyne incognita and Plant Growth Promoter - Sembiring, Ade Indra Maulana; Giyanto; Supramana (Jurnal Fitopatologi Indonesia, 2024)
Effectiveness of the Bioactive Compound from Metagenomic Library Clones as Biocontrol of Meloidogyne incognita and Plant Growth Promoter Metagenomics is a technique for exploring the genetic diversity of microbes in an environment, including those that can act as biocontrol agents. This research aims to determine the effectiveness of bioactive compounds produced by the isolates of metagenomic library clones from cocoa (PMP7, PMC8, PMS14, PMC3, PMC13, PMC14, and PMS11) as agents for controlling root knot nematode Meloidogyne incognita and promoting plant growth. In vitro testing was carried out using filtrates of bioactive compounds from seven metagenomic library clones on juvenile 2 nematodes in petri dishes. Nematodes treated with bioactive compounds were incubated at 27 ℃ and their mortality was observed 24 hours after treatment. The physiological characterization carried out on the clone isolates involved the production of HCN, chitinase and protease enzymes. In planta testing was carried out on cucumber plants var. Kitoh which were planted in polybags. Juvenile 2 nematodes were infested in each polybag and bioactive compound was given by watering the suspension at 14 and 30 days after planting. Observations were conducted every week until galls were formed on the plant roots. The results showed that seven isolates of metagenomic library clones had nematicidal effect with an in vitro mortality rate of 96%–100% and were able to produce protease enzymes with a proteolytic index of 0.13–0.6. In the in planta test, PMS11 isolate was able to suppress the severity of root knots with suppression effectiveness reaching 54.63%. Two isolates, i.e. PMC8 and PMS14, showed the best ability to stimulate plant growth.